Analisis Dinamik Model Penyebaran COVID-19 dengan Vaksinasi - Resmawan, Resmawan; Yahya, Lailany; Pakaya, Revandi S.; Panigoro, Hasan S.; Nuha, Agusyarif Rezka (Jambura Journal of Biomathematics (JJBM), 2022)
Coronavirus Disease 2019 (COVID-19) is a new type of virus from a large family of viruses transmitted between humans and animals (zoonotically transmitted) that was first discovered in Wuhan City, Hubei Province, China in late 2019 which is still widespread and threat throughout the world including Indonesia. This article discussed about the mathematical model of the spread of COVID-19 with vaccinations. In this case, the human population is divided into 5 classes, namely the suspected, vaccine, exposed, infected and recovered classes. The constructed model forms an SVEIR model that has two equilibrium points, namely disease-free and endemic equilibrium points. Stability analysis shows that the equilibrium point is stable local and global asymptotic if R0 1 and unstable if R0 1. Then a sensitivity analysis was carried out to determine the parameters that greatly affect the model as well as furthermore, numerical simulations are given to describe the behavior of the model that has been obtained based on the analysis of the sensitivity of basic reproductive numbers, obtained several parameters that affect the spread of COVID-19. Numerical simulation results show that vaccination can suppress the addition of infected populations and depend on the level of effectiveness of vaccination.